An Effective Process for Removing Acrylonitrile from Wastewater - Jing1, Guolin; Wei1, Shirong; Du2, Jing (Asian Journal of Chemistry, 2014)
The aim of this paper was to study the suitability of catalytic wet air oxidation for the treatment of wastewater containing 4000 mg/L acrylonitrile. Experiments were conducted in a 0.5 L high pressure batch reactor using Cu(NO3)2 as homogeneous catalyst. Temperature, oxygen dose, catalyst concentration and residence time have been caried from 483 to 523 K, 7.67-61.32 g/L, 50 to 250 mg/L and 1-9 min, respectively. The 250 mg/L Cu2+ catalyst performs chemical oxygen demand, total organic carbon and acrylonitrile conversions over 97.23, 97.78 and 94.87 % after 9 min reaction at 523 K and 38.33 g/L O2 dose. Catalyst concentration was found to have a significant impact on the oxidation of acrylonitrile wastewater. The results obtained in this work indicated that the catalytic wet air oxidation was an effective pretreatment method for the acrylonitrile wastewater.